Precedence Metric Constructed Ad Hoc Direction-Finding For Submerged Radar Networks - Venkatesan, T; Sunitha, R (International Journal of Computer Sciences and Engineering, 2025)
This paper investigates applications and challenges at that point a pick up submerged sensor at that point a pick up networks. We highlight potential applications to off-shore oilfields at that point a pick up seismic monitoring, hardware monitoring, and submerged robotics. We identify relook headings in short- range acoustic communications, MAC, time synchronization, and limitation conventions at that point pick up high-idleness acoustic networks, long- length of time framework sleeping, and application-level data scheduling. We depict our preparatory arrangement on short-run acoustic correspondence hardware, and summarize results of high-idleness time synchronization